Basal plane bending of 4H-SiC single crystals grown by sublimation method with different seed attachment methods. Issue 43 (18th October 2018) - Yang, Xianglong; Yu, Jinying; Chen, Xiufang; Peng, Yan; Hu, Xiaobo; Xu, Xiangang; Yang, Xianglai; Song, Yingxin; Wang, Ruiqi
Abstract : Basal plane bending of 4H-SiC single crystals grown using the sublimation method on an open or closed backside seed was measured using high-resolution X-ray diffractometry. Abstract : Basal plane bending of 4H-SiC single crystals grown using the sublimation method on an open or closed backside seed was measured using high-resolution X-ray diffractometry. In order to allow full information to be obtained about the complexity of basal plane bending, line scans of the 0004 reflection rocking curves were carried out on the (0001) Si face along the <11−20>, <10−10>, <2−1−10>, <1−100>, <1−210> and <0−110> directions. The measurement results revealed the seed attachment had a pronounced effect on the basal plane bending behaviors. The single crystals grown on a closed backside seed exhibit strong basal plane bending which is rotationally symmetric and concave towards the growth direction. However, the single crystals grown on an open backside seed show much weaker basal plane bending. The basal plane bending inheritance of 4H-SiC single crystals grown by sublimation with two different seed attachment methods was studied. Moreover, the basal plane bending characteristics of 4H-SiC crystals grown on an open backside seed with apparent axisymmetric basal plane bending were investigated. Molten KOH etching was carried out to correlate the basal plane bending with the distribution of structural defects to understand the basal plane bending mechanism. Finally, the effect of macroscopic shear stress resulting from the difference in the thermal expansion coefficient between the silicon carbide (SiC) seed and graphite holder and the induced structural defects on the basal plane bending of 4H-SiC single crystals was explored.